2017
DOI: 10.1063/1.4973830
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear density excitations in electron-positron-ion plasmas with trapping in a quantizing magnetic field

Abstract: In the present work, we have investigated the effect of trapping as a microscopic phenomenon on the formation of solitary structures in the presence of a quantizing magnetic field in an electron-positron-ion (e-p-i) plasma having degenerate electrons and positrons, whereas ions are taken to be classical and cold. We have found that positron concentration, quantizing magnetic field, and finite electron temperature effects not only affect the linear dispersion characteristics of the electrostatic waves under con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This is the Landau quantization, which is generally taken into consideration when the electron thermal energy is assumed to be much smaller compared to the electron cyclotron energy [viz., k B T e = ÿω ce ],whereT e andω ce denote the electron temperature and electron cyclotron frequency, respectively, with Boltzmann constantk B and scaled Planck constant ÿ. In recent past, Iqbal et al [37] considered an EPI cold plasma to investigate the ion-acoustic (IA) waves in the presence of electron-positron quantization effects. They carried out a parametericinvestigation and analyzed the linear and nonlinear characteristics of the IA waves, investigating the effects of the quantized magnetic field, positron concentration and electron temperature on the compressive solitary structures.…”
Section: Introductionmentioning
confidence: 99%
“…This is the Landau quantization, which is generally taken into consideration when the electron thermal energy is assumed to be much smaller compared to the electron cyclotron energy [viz., k B T e = ÿω ce ],whereT e andω ce denote the electron temperature and electron cyclotron frequency, respectively, with Boltzmann constantk B and scaled Planck constant ÿ. In recent past, Iqbal et al [37] considered an EPI cold plasma to investigate the ion-acoustic (IA) waves in the presence of electron-positron quantization effects. They carried out a parametericinvestigation and analyzed the linear and nonlinear characteristics of the IA waves, investigating the effects of the quantized magnetic field, positron concentration and electron temperature on the compressive solitary structures.…”
Section: Introductionmentioning
confidence: 99%
“…Shah et al found the expression for adiabatically trapped number density of electrons by virtue of an electrostatic scalar potential in the limits of partially and fully degenerate plasmas which we will use in our problem [27]. The effect of adiabatic trapping on the dispersion properties of ion acoustic waves in degenerate plasmas and relativistic degenerate plasmas in the presence of quantizing magnetic field were studied to obtain both compressive and rarefactive solitary solutions via Sagdeev potential approach and tangent hyperbolic (tanh) method [28][29][30]. Furthermore, drift solitary waves with trapped electrons have also been studied for the variation of electron degeneracy temperature in dense astrophysical plasmas [31].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the quantum electron-ion or electron-positron-ion magnetoactive plasmas are common in planetary interiors, in compact astrophysical objects [5], as well as in the next generation intense laser-solid density plasma experiments. Various aspects of linear and nonlinear propagation characteristics of electrostatic or electromagnetic modes in the context of isotropic Fermi surfaces have been investigated in numerous papers [6][7][8][9][10][11][12][13][14]. However, as is well known, the concept of spherical symmetry of the Fermi surface is no more valid in certain systems even in a collisionless regime of Fermi gas [15,16].…”
mentioning
confidence: 99%
“…Employing the quantum kinetic equation derived in Ref. [10] the dispersion properties of various modes have been discussed in quantum plasmas [10][11][12][13][14]24].…”
mentioning
confidence: 99%